Geographical distribution of vampire bat-related cattle rabies in Brazil - Kobayashi, Yuki; Ogawa, Ai; Sato, Go; Sato, Tetsuo; Itou, Takuya; Samara, Samir I.; Carvalho, Adolorata A. B.; Nociti, Darci P.; Ito, Fumio H.; Sakai, Takeo (Japan Soc Vet Sci, 2006)
Seventy-seven rabies virus (RV) isolates originating from Brazilian cattle were genetically characterized. Partial nucleoprotein gene sequences of these isolates were phylogenetically and geographically analyzed. Cattle isolates, which clustered with the vampire bat-related RV group, were further subdivided into nine genetic subgroups. These subgroups were distributed widely in lowland regions, with some subgroups separated from each other by mountain ranges. In addition, separation of the groups in mountainous regions was correlated with altitude. These results indicate that cattle rabies is derived from several regionally-defined variants, which suggests that its geographical distribution is related to that of the vampire bat population.
Keywords: Cattle; geographical analysis; rabies